2021
DOI: 10.3390/rs13101961
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Mangrove Zonation Changes in Senegal with Landsat Imagery Using an OBIA Approach Combined with Linear Spectral Unmixing

Abstract: The mangrove areas in Senegal have fluctuated considerably over the last few decades, and it is therefore important to monitor the evolution of forest cover in order to orient and optimise forestry policies. This study presents a method for mapping plant formations to monitor and study changes in zonation within the mangroves of Senegal. Using Landsat ETM+ and Landsat 8 OLI images merged to a 15-m resolution with a pansharpening method, a processing chain that combines an OBIA approach and linear spectral unmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
(100 reference statements)
0
5
0
Order By: Relevance
“…For land cover classification, satellite images can be analyzed by grouping pixels or objects with similar characteristics based on statistical or mathematical relationships [1]. The unsupervised machine learning algorithm utilized for mangrove mapping is ISODATA [18], [19].…”
Section: Image Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…For land cover classification, satellite images can be analyzed by grouping pixels or objects with similar characteristics based on statistical or mathematical relationships [1]. The unsupervised machine learning algorithm utilized for mangrove mapping is ISODATA [18], [19].…”
Section: Image Classificationmentioning
confidence: 99%
“…This approach analyzes a group of pixels based on comparable spectral features [1]. In mangrove mapping studies, these two approaches are combined with supervised [31], [33] or unsupervised machine learning methods [18], [19]. Based on the literature review, various machine learning algorithms have been employed and demonstrated their performance in mangrove mapping tasks.…”
Section: Image Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The related features of different land objects, including spectral, context, and shape features, are extracted for the different land objects [ 18 ]. OBIA has been widely used in remote sensing image analysis [ 19 , 20 , 21 , 22 , 23 , 24 ]. The basic processing unit of the OBIA method is the object, which differs from methods based on the object’s pixels [ 25 ], and thus, OBIA has been determined to have a great uncertainty in terms of image processing.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, pansharpening represents a crucial step in the production of images aimed at visual interpretation in widely exploited software such as Google Earth and Bing Maps. Likewise, many other applications take advantage of this kind of fused data, for instance, agriculture (e.g., for crop type [6] and tree species [7] classification and for precision farming [8]), land cover change detection (e.g., for snow [9], forest [10] and urban [11] monitoring), archaeology [12] and even space mission data analysis [13].…”
Section: Introductionmentioning
confidence: 99%